PEMANFAATAN LIMBAH JERUK LIMAU DALAM PEMBUATAN SABUN CUCI PIRING DI DESA SUKAPURA - Tatang Mulyana1,Sinta Rahayu2, Chantika Tazri Agnia3 (Politeknik Seruyan, 2024)
Lime waste in Sukapura Village is often not used by the community but is often thrown away as rubbish. In fact, limes contain the compound limonene which has an active ingredient that can be used as a cleaner such as dish washing soap. This program is a community service activity carried out by KKN students at Winaya Mukti University. This activity aims to help the community to be actively involved in solving the problem of agricultural waste so that it becomes a product that has added economic value. The method used is direct outreach and training to lime farmers. The results of this community empowerment activity show that the use of lime waste can provide added economic and environmental value for the people of Sukapura village. Key Words: Limes Waste, Empowerment, Added Value,Dish Washing Soap